2021
DOI: 10.3892/etm.2021.9869
|View full text |Cite
|
Sign up to set email alerts
|

Kuwanon G protects HT22 cells from advanced glycation end product-induced damage

Abstract: The incidence of diabetic encephalopathy is increasing as the population ages. Evidence suggests that formation and accumulation of advanced glycation end products (AGEs) plays a pivotal role in disease progression, but limited research has been carried out in this area. A previous study demonstrated that Kuwanon G (KWG) had significant anti-oxidative stress and anti-inflammatory properties. As AGEs are oxidative products and inflammation is involved in their generation it is hypothesized that KWG may have eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
0
2
0
1
Order By: Relevance
“…This study aimed to identify the natural-product-derived compounds and their derivatives exhibiting autophagy inhibitory activity by using phenotypic-based screening. The high-content image analysis screen identified Ka-003, a derivative of methyl cyclohexene (Figure 5), resembling those found in mulberry plants [31][32][33][34][35], as enabling a potent decrease in the number of autophagic vacuoles in cells in a dose-dependent manner (Figures 1 and 2). More importantly, upon the application of the Ka-003 treatment to DENV-infected cells, a dose-dependent decrease in DENV infectious particle production was observed (Figures 3 and 6).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This study aimed to identify the natural-product-derived compounds and their derivatives exhibiting autophagy inhibitory activity by using phenotypic-based screening. The high-content image analysis screen identified Ka-003, a derivative of methyl cyclohexene (Figure 5), resembling those found in mulberry plants [31][32][33][34][35], as enabling a potent decrease in the number of autophagic vacuoles in cells in a dose-dependent manner (Figures 1 and 2). More importantly, upon the application of the Ka-003 treatment to DENV-infected cells, a dose-dependent decrease in DENV infectious particle production was observed (Figures 3 and 6).…”
Section: Discussionmentioning
confidence: 79%
“…As mentioned above, Ka-003 is a derivative of methyl cyclohexene that resembles those found in mulberry plants [31][32][33][34][35]. These include kuwanon G, kuwanon H, kuwanon X and mulbenofuran C. Kuwanon G treatment was previously shown to decrease ROS levels in LPS-treated Caco-2 cells, resulting in the reduced production of proinflammatory cytokines, including IL-1β and TNF-α, and increased cell survival [31].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it was observed that there was upregulation of pentosidine and a concomitant decrease in the anti-oxidant systems including vitamin E ( Lapolla et al, 2007 ). Levels of glutathione peroxidase and SOD were also found to be diminished in in vitro diabetic encephalopathy model, HT22 cells ( Gan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…M. alba is also used as an herb in traditional Chinese medicine. Secondary metabolites of M. alba have been proved to have multiple physiological activities, including antiviral, antibacterial, and anti-inflammatory activities [ 15 , 16 , 17 , 18 , 19 ]. To better illustrate the regulation mode of flavonoid biosynthesis and lignin biosynthesis in M. alba leaves under different stresses, we treated M. alba leaves using two kinds of stress: B. cinerea infection, which is biotic stress, and high-level UV-B radiation, which is abiotic stress.…”
Section: Introductionmentioning
confidence: 99%